Induction of heartwood formation in young Indian sandalwood (Santalum album L.) by gas elicitors - Liu, Xiaojin; Zhang, Qilei; Hong, Zhou; Xu, Daping (Frontiers in Plant Science, 2022)
Induction of heartwood formation in 6-year-old Indian sandalwood (Santalum album L.) trees by treatment with carbon dioxide, ethylene, nitrogen and wounding was investigated. All treatments induced fragrant heartwood formation upward and downward from the drill hole. The amount of heartwood formed above and below the drill hole depended on the treatment in the order nitrogen>carbon dioxide>ethylene>wounding, while the radial extension proportion was, in order, nitrogen>carbon dioxide>ethylene=wounding. Based on chemical analysis (GC–MS) and evaluation of the essential oil quality and heartwood properties, heartwood induced by carbon dioxide showed the maximum similarities to naturally formed heartwood, which included the same color, similar chemical composition, reasonable oil content and quality essential oil, whereas ethylene, nitrogen and wounding treatment showed fewer similarities to natural heartwood. The results suggest that carbon dioxide is a promising candidate gas elicitor for inducing heartwood formation in young S. album.